The awareness of obesity associated comorbidities among normal weight, overweight and obese individuals: a cross sectional analysis - Nizameddin Koca; Koray Ayar; Canan Ersoy (SERNEV, 2018)
Introduction: Obesity is one of the most important community healththreatening problem, because of its high prevalence and associatedcomorbidities. Each of these comorbidities have various risks for health. Thereare very few studies investigating the awareness of people about obesityassociated comorbiditiesMethods: Five-hundred adult patients, admitted to Endocrinology amp; Internal Medicine outpatient clinics, whose body mass index was gt;18.5kg/m2 and completed a questionnaire concerning obesity associatedcomorbidities were included in this study. Each correct answer was scored as 1point. Each participant's total score and mean total score (MTS) wascalculated. The scores among normal weight, overweightand obese groups were compared. Besides the questionnaire, age, gender,education level was asked and waist and hip circumference, height and weightwere measured by the researchers.Results: Mean education scorewas the lowest in the obese group, altough MTS was the highest. Awareness of obesity associated stroke, breast cancerand osteoarthritis were significantly higher in the obese group when comparedto the other groups, but there was no difference between men and women. Awarenessof obesity associated menstrual irregularity and infertility was higher inwomen, hypertension and prostate cancer was higher in men.Conclusions: Although the education level was lowest in the obesegroup, the awareness of obesity-associated comorbidities was highest.